3D morphology design for forward osmosis - Shi, M; Printsypar, G; Duong, P; Calo, V; Iliev, O; Nunes, S (Elsevier, 2016)
We propose a multi-scale simulation approach to model forward osmosis (FO) processes using substrates with layered homogeneous morphology. This approach accounts not only for FO setup but also for detailed microstructure of the substrate using the digitally reconstructed morphology. We fabricate a highly porous block copolymer membrane, which has not been explored for FO heretofore, and use it as the substrate for interfacial polymerization. The substrate has three sub-layers, namely a top layer, a sponge-like middle layer, and a nonwoven fabric layer. We generate a digital microstructure for each layer, and verify them with experimental measurements. The permeability and effective diffusivity of each layer are computed based on their virtual microstructures and used for FO operation in cross-flow setups at the macro-scale. The proposed simulation approach predicts accurately the FO experimental data.